(untitled) (Research, Society and Development, 2021)
Introduction: The occurrence of deaths due to drug intoxication has been considered one of the public health problems. Objective: To describe the main determinants of drug poisoning in the city of Teresina-PI. Methodology: Ecological, descriptive, quantitative and population-based research, with a study of poisoning by drugs reported in the city of Teresina-PI, from 2010 to 2019 by the Ministry of Health/SINAN. The following data were collected: gender, ethnicity, education, age group, clinical evolution, final classification, circumstance, confirmation criteria and the municipality of residence in Piauí. 2019. Results and discussion: In the period analyzed, 2,229 occurrences were recorded, with the predominant ethnicity (41.36%), education with complete high school (12.43%), age group 20-39 (43.43%) and female (73.44%). As for the type of exposure to acute-chronic, it occurred in 1287 records (57.74%), and the criterion for confirmation was clinical (64.56%). The most frequent circumstance was attempted suicide (71.02%) and the final clinical outcome was cure with no damage (59.22%). Conclusion: It was found that in the city of Teresina-PI there was an increase in notifications, this fact can be attributed to the pattern of drug consumption. In general, Health Surveillance must prioritize professional sensitivity to obtain more educational, preventive and intersectoral actions to ensure the improvement of health surveillance policies.